Oncolytic Viruses - Genetically Engineering the Future of Cancer Therapy - Benjamin Gesundheit (Frontiers Research Topics, 2017)
The ability to genetically engineer oncolytic viruses in order to minimize side effects and improve the selective targeting of tumor cells has opened up novel opportunities for treating cancer. Understanding the mechanisms involved and the complex interaction between the viruses and the immune system will undoubtedly help guide the development of new strategies. Theranostic biomarkers to monitor these therapies in clinical trials serve an important need in this innovative field and demand further research.